2020
DOI: 10.1007/s13224-020-01404-7
|View full text |Cite
|
Sign up to set email alerts
|

Retroperitoneal angioleiomyomatosis

Abstract: Retroperitoneal intravenous leiomyomatosis is a rare benign tumor that can spread through veins carrying significant morbidity. The challenge of its management lies within the complexity of completely excising the tumor, which if carried out improperly can result in neurological or vascular complications requiring complex reparative surgeries. Here we present the successful resection of a retroperitoneal angio-leiomyoma by combining laparoscopic route, micro-surgical techniques and modern endoscopic tools.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Our findings are similar to other studies showing that contained morcellation is a feasible and safe method to retrieve large benign surgical specimens and for suspected cases of cancer. There were no intraoperative complications or postsurgical hernias at the port sites [21,43,[47][48][49]. We found that giant tumors (>1000 g) required greater skills for manipulation, thus reducing the possibility of cell spreading without significantly increasing the surgical time when compared with tumors less than 500 g. Two cases of puncture occurred; one of them was noticed immediately when the morcellator blade scraped one edge of the bag and only required the bag to be repositioned.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Our findings are similar to other studies showing that contained morcellation is a feasible and safe method to retrieve large benign surgical specimens and for suspected cases of cancer. There were no intraoperative complications or postsurgical hernias at the port sites [21,43,[47][48][49]. We found that giant tumors (>1000 g) required greater skills for manipulation, thus reducing the possibility of cell spreading without significantly increasing the surgical time when compared with tumors less than 500 g. Two cases of puncture occurred; one of them was noticed immediately when the morcellator blade scraped one edge of the bag and only required the bag to be repositioned.…”
Section: Discussionmentioning
confidence: 75%
“…The markers HHV-8, S100, synaptophysin, and calretinin were negative. The cytology of peritoneal fluid showed mild subacute inflammation with activated mesothelial cells suggestive of exudative peritoneal effusion [21]. The peritoneal washing cytology examination of all specimens did not show any case of malignancy or tissue spillage (Table 4).…”
Section: Resultsmentioning
confidence: 93%